Small Micro Enterprises: A Review of Service Quality and Customer Satisfaction - Wahyuningsih, Sri; E, Sotya Partiwi; Marlini, Wenny; Alwi, M. Takhiyuddin (Politeknik Piksi Ganesha Indonesia, 2024)
Walik Ahjib Tofu is one of the MSEs located at Manunggal Gombong Square. Walik Ahjib Tofu's strategic location and delicious variant flavors make it a popular dish, but its service leaves consumers feeling less satisfied due to the lengthy queues. This study aims to determine how satisfied MSEs Tahu Walik Ahjib Manunggal Gombong consumers are with the services provided. The study employed a descriptive quantitative method, utilizing a g.form questionnaire, which was completed by 98 respondents. The results showed that customer satisfaction was influenced by service quality factors (physical evidence variables): reliability, responsiveness, assurance, and empathy, which had a positive effect based on the f-square test and were significant based on statistical tests. The results of this study indicate that the five service quality variables have a significant impact on customer satisfaction with Walik Ahjib Manunggal Gombong Tofu MSEs. The most influential factor is responsiveness.